First Aid in the Prevention and Treatment of Chemical Casualties - United States. Office of Civilian Defense (United States. Office of Civilian Defense, 1941)
Illustrated throughout, this booklet includes sections on lung irritants, blister and tear gases, irritant smokes, incendiaries, screening smokes, systemic poisons and decontamination stations.
Keywords: Gases, Asphyxiating and poisonous; First aid in illness and injury; Chemical warfare; United States. Office of Civilian Defense